The Expression of Matrix Metalloproteinases Activated Differently on In-Vitro Maturation of oocytes Cytoplasm and Cumulus Cells in Bovine - Sang-Hwan Ki; Jong-Taek Yoon (Journal of Animal Reproduction and Biotechnology, 2018)
To determine the differences in the in-vitro ovum maturation process of bovine, we compared the expression of MMPs in these oocytes and cumulus cell throughout oocytes maturated. In an attempt to investigate the effect of MMP activation and inhibitors in total protein of cumulus cell and, oocytes during oocytes maturation, we examined and monitored the localization and expression of MMPs (MMP-2 and MMP-9), TIMPs (TIMP-2 and TIMP-3), as well as their expression profiles (Real-time PCR, Gelatin Zymography and ELISA). Our results that the bovine oocytes MMP-2 and MMP-9 level was significantly associated with the rate of maturity of oocytes (P<0.05). In cumulus cell, MMP-2 was highly expressed in all stages of the oocyte’s maturation. The final oocytes maturation exhibited strong gelatinase activity. There was no significant correlation between cumulus cell MMP-9 and the maturation rate of oocytes. However, for the oocyte cytoplasm MMP-9 expression was significant correlation to the maturation oocytes. There was no significant correlation between cumulonimbus cells MMP-9 and oocyte maturation rates; however, for oocyte cytoplasm, MMP-9 expression was significantly correlated with mature oocyte. However, the TIMP-1 and TIMP-2 protein expression patterns are not correlated with the maturation rate of the oocyte. Our results suggest that MMP different expression pattern may regulate the morphological remodeling of oocyte's in the cumulus cell. Further, the MMP-2 expression has a strong relation with a higher maturation rate of the oocyte.